Intentional Presentation of Objects in Cooperatively Breeding Arabian Babblers (Turdoides squamiceps) - Ben Mocha, Yitzchak; Pika, Simone (Frontiers in Ecology and Evolution, 2019)
The emergence of intentional communication and, furthermore, the intentional presentation of objects are important steps in the ontogeny of cooperative communication in humans. Intentional object presentation is an extremely rare form of communication evolutionarily. Research on comparable means of communication in nonhuman species may therefore shed light on distinct selection pressures that acted upon components of human communication. However, the functions and cognitive mechanisms that underlie object presentation in animals are poorly understood. Here, we addressed these issues by investigating object presentation in wild, cooperative breeding Arabian babblers (Aves: Turdoides squamiceps). Our results show that individuals present an object to a specific recipient. The recipient most often responds by approaching the signaler and the dyad then moves jointly to copulate at a hidden location. We provide evidence that object presentation by Arabian babblers: (i) is not a costly signal, as objects were not costly to acquire; (ii) birds do not trade food for sex, as the presentation of food was not more likely to result in copulation; and (iii) that presentations possess the hallmarks of first-order intentionality. These results show that intentional presentation of objects is not restricted to the primate linage and may suggest that the need to engage in cooperative interactions facilitates elaborate socio-cognitive performances.